Meta-analysis of the effect of black soldier fly larvae meal in diet on broiler performance and prediction of its metabolisable energy value - Andrés L. Martínez Marín; Marta Gariglio; Ilaria Biasato; Laura Gasco; Achille Schiavone (Italian Journal of Animal Science)
The aims of the present work were to determine by meta-analysis the responses of broiler performance to increasing dietary levels of black soldier fly larvae meal (BSFLM) and to develop prediction models of the apparent metabolisable energy corrected to zero nitrogen balance (AMEn) of BSFLM. Eighteen studies from 12 countries that sum up to 20 experiments and involved a total of 63 treatments with 468 replicates and 4229 birds fulfilled the requirements for the meta-analysis. Four papers from three countries that investigated eight different samples of BSFLM were selected for development of AMEn prediction by means of regression analysis or artificial neural network (ANN) modelling. Growth performance results were not affected (p > .05) by the presence of BSFLM at levels of 5.7 ± 2.3 and 15.5 ± 6.0% in the diet. Multiple linear regression and ANN models showed high precision and accuracy, were unbiased and performed almost identically in the evaluation dataset (R2 = 0.856 and 0.858 and root mean square error of prediction as percentage of the observed mean = 5.216 and 5.241%). Feeding broilers with diets containing 15% BSFLM is not expected to have negative effects on growth performance. The following regression model could be useful for the estimation of AMEn in BSFLM: AMEn = 4.08 (± 0.330) + 0.295 (± 0.0158) × GE + 0.186 (± 0.0021) × EE; where AMEn and gross energy (GE) are MJ/kg dry matter and crude fat (EE) is % dry matter.